The Effect of Training and Development Programs on Employee Performance PT. Victoria Care Indonesia - Rajasa, Resta; Pradila, Tasa; Pratama, Yuda; Putra, Rafa Dwi; Ramadhan, Wafa Aulia Fazri; Rifai, Asep Achmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Over time, a company or organization must innovate and refresh its human resources (HR), including providing training and development programs for its employees. Through training and development programs, it is hoped that human resources will be able to compete with other companies in all aspects. The purpose of this article is to see the effectiveness of the results of training and development organized by PT Victoria Care Indonesia. The writing method uses observation and interview methods through descriptive literature. From the results of observations, it is known that training and development programs can improve employee performance to achieve company goals according to predetermined targets